The emperor's new clothes: a big book of fairy tales series (Al Asad publications Lahore, 2008)
In *The Emperor's New Clothes* by Hans Christian Andersen, an emperor is tricked by two swindlers who claim to make him an invisible suit only wise people can see. The emperor, too proud to admit he can't see the clothes, parades in his "new" outfit. A child in the crowd finally points out that the emperor is wearing nothing at all, revealing the truth.